Development and validation of diagnostic and activity-assessing models for relapsing polychondritis based on laboratory parameters - Liu, Yongmei; Cheng, Linlin; Zhao, Mengzhu; Zhan, Haoting; Li, Xiaomeng; Huang, Yuan; Li, Haolong; Hou, Yong; Li, Yongzhe (Frontiers in Immunology, 2023)
Background: Relapsing polychondritis (RP) as a rare autoimmune disease is characterized by recurrent inflammation of organs containing cartilage. Currently no biomarkers have been integrated into clinical practice. This study aimed to construct and evaluate models based on laboratory parameters to aid in RP diagnosis, assess activity assessment, and explore associations with the pathological process. Methods: RP patients and healthy controls (HCs) were recruited at the Peking Union Medical College Hospital from July 2017 to July 2023. Clinical data including Relapsing Polychondritis Disease Activity Index (RPDAI) score and laboratory tests were collected. Differences of laboratory data between RP patients and HCs, active and inactive patients were analyzed. Results: Discovery cohort (cohort 1) consisted of 78 RP patients and 94 HCs. Model based on monocyte counts and neutrophil to lymphocyte ratio (NLR) could effectively distinguish RP patients from HCs with an AUC of 0.845. Active RP patients exhibited increased erythrocyte sedimentation rate, complement 3, platelet to lymphocyte ratio (PLR), NLR, and C-reactive protein to albumin ratio (CAR) compared to stable patients, which were also positively correlated with RPDAI. Notably, CAR emerged as an independent risk factor of disease activity (OR=4.422) and could identify active patients with an AUC of 0.758. To confirm the reliability and stability of the aforementioned models, replication cohort (cohort 2) was enrolled, including 79 RP patients and 94 HCs. Monocyte combined NLR, and CAR showed a sensitivity of 0.886 and 0.577, specificity of 0.830 and 0.833, in RP diagnosis and activity prediction, respectively. Furthermore, lower natural killer cell levels in RP patients and higher B cell levels in active patients may contribute to elucidating pathological mechanisms of disease occurrence and exacerbation. Conclusions: The utilization of laboratory parameters provides cost effective and valuable markers that can assist in RP diagnosis, identify disease activity, and elucidate pathogenic mechanisms.